Covert Amish investigation [large type] - Lynn, Dana R. (Lynn, Dana R. Amish country justice., 2021)
"After a woan in witness protection disappears from Kate Bontrager's Amish hometown, the now Englisch police officer goes undercover--and enters a killer's sights. Partnering with Abram Burkholder, the man she'd hoped to marry nearly a decade ago, is the only way to solve the case. But can they face the past and heal their still damaged hearts...before they both end up dead?"--